2020
DOI: 10.1007/s41247-020-00073-4
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic and Environmental Assessment of Power Supply Chain by Using Waste Biomass Gasification in Iceland

Abstract: In this paper, technical, economic and environmental assessments are carried out for power supply chain by using timber and wood waste (T&WW) gasification in Iceland. The Icelandic municipalities were clustered into 35 subgroups based on various number of households/ inhabitants. Different expenses were taken into consideration, like capital, installation engineering, operation and maintenance costs and the interest rate of the investment. Regarding revenues, they come from the electricity sale and the fee pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The combination of these two modules represents the behavior of a combustion engine where the reaction with air occurs[13] [14]. The inputs values and key assumptions used in this work are based on our waste biomass gasification simulation model developed by ASPEN Plus[8] and the main values of the downdraft gasifiers characteristics, operational parameters and the flue gas composition are relied on our previous work[15].…”
mentioning
confidence: 99%
“…The combination of these two modules represents the behavior of a combustion engine where the reaction with air occurs[13] [14]. The inputs values and key assumptions used in this work are based on our waste biomass gasification simulation model developed by ASPEN Plus[8] and the main values of the downdraft gasifiers characteristics, operational parameters and the flue gas composition are relied on our previous work[15].…”
mentioning
confidence: 99%
“…They found that a gasification‐based power plant is more attractive and economical in comparison to combustion‐based power plants. The biomass gasifier model, with the help of Aspen Plus software, has been developed by Safarian et al 67 to investigate the effect of biomass type (timber and wood) on output, and the biomass gasifier energy system's electrical efficiency was found to be very sensitive toward moisture content. Arena et al 68 have done a comparative analysis between gas turbine and IC engine‐based biomass gasifier energy system for electricity production in the range of 100 to 600 kW.…”
Section: Various Combinations Of Biomass Hresmentioning
confidence: 99%
“…Garden waste is transferred from the waste fields to the preparation/pre-processing part, which is next to the gasification and ethanol production unit. The gasification process consists of drying, pyrolysis, combustion, and reduction [13,14]. Typically, the moisture in biomass ranges from 5-35%, which is reduced to lower than 5% through the drying process which occurs at a temperature of 100-150 • C. Then, in the pyrolysis step, biomass is heated (it is in the range of 200-700 • C) in the absence of oxygen; then, its volatile components are vaporized.…”
Section: System Descriptionmentioning
confidence: 99%